Quantification and Evaluation of Soil Erosion in the Estuaries of Cameroon, Gulf of Guinea: Case of Nylon Area - Eric Flavien Mbiakouo-Djomo; Ebénézer Njeugna; Denis Tcheukam-Toko; Didier Fokwa (Applied and Environmental Soil Science)
The area of Nylon represents a sensible and vulnerable environment where water erosion is the cause of many soil losses contributing to the production and movement of sediments from the upstream to the lowest depths. The high level of rainfall in this town, soil texture (sand-clay-silt), and the anarchic occupation of the area play a part in the important deterioration of the bare ground on the upstream of the catchment area. This causes with time an instability of structures and living places which can lead to their progressive disappearance. In order to assess the quantities of displaced sediments, the studies on the quantification of soil moved annually by water erosion are carried out. A direct method is used consisting in using a minisimulator of rain (NEME) in order to understand the phenomena involved and assess the quantity of sediments which can be moved. It helps in assessing erosion caused by the rain and extrapolating results over the catchment area of the chosen field of study. USLE relation has permit to make an extrapolation of the quantity of soil affected, and the result shows that the average potential of loss of soil is 153.57 t/ha/annum.